ANALISIS FI’IL TSULASI MUJARRAD DALAM KITAB AKHLAK LIL BANIN JILID II: KAJIAN TATA BAHASA ARAB DAN IMPLIKASINYA PADA PENDIDIKAN AKHLAK ANAK - Shabilla Amelya; Ihin Solihin (Jurnal Sathar, 2025)
This study examines the use of fi’il tsulasi mujarrad in the Book of Morals Lil Banin Volume II with a focus on the structure of Arabic grammar and its relevance to the formation of children's characters. This study identifies the dominant patterns of fi’il tsulasi mujarrad used in the delivery of moral values, analyzes the grammatical function of each form of verb, and explains how the selection of the language structure affects the effectiveness of internalizing moral values in students. Through a qualitative approach with the literature study method, the research found that the use of fi’il tsulasi mujarrad is not just a linguistic choice, but a pedagogical strategy that makes it easier for children to understand moral commands and prohibitions directly. The results of the study showed a strong correlation between the simplicity of verb morphological structure and the absorption of moral value understanding in early childhood students.